Phylogeographic pattern of Jenynsia multidentata (Cyprinodontiformes: Anablepidae) in the southern boundary of the Brazilian Subregion, Argentina - Bruno, María Cecilia (2013)
The Atlantic drainage basins are located in the southern Pampean area, in the southernmost part of the Brazilian subregion. Tectonic and paleoclimatic phenomena, occurring during the Quaternary, have currently isolated these basins from the present hydrographic system. Their ichthyofaunal composition is similar to that of hydric systems located further northward. Jenynsia multidentata is a species with wide distribution in the Atlantic drainage basins, as well as in those Northern basins. Here we investigated the phylogeographic pattern of Jenynsia multidentata and analyzed its relationships with the paleoclimatic and geologic history of the region. The analysis of the population’s assemblage showed moderate genetic diversity, demographic equilibrium and marked genetic structure in the populations that occupy the extremes of the distributional range. The populations in the center of the range did not present genetic diversity, sharing a single haplotype. These results allow inferring that the presence of Jenynsia multidentata in the area results from historical demographic processes that are independent but complementary. In turn, these processes could arise from paleoclimatic changes occurred during the Quaternary.